(3ehLR aj GdbQGAGJ ef WQjb GdSHYIs - (3GdMSf Hf Ydj Hf EHQGgje Hf jROGO GdCghGRj, CHh Ydj,J (B446 (3g` s
(3ChdgG (B:s
(3gPG cJGH ehLR aj TQM GdbQGA GdSHYI deDdag Hf cKHQ Gdeci s
(3BNQgG (B:s
(3HVe GdaGA eY GdgeRI h Gddg CYde HGdUhGH h Edjg GdeQLY h GdeBH s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B245 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B247s
Keywords: (3GdbQGAGJ hGdJLhjOs